2016
DOI: 10.35790/ecl.4.2.2016.14501
|View full text |Cite
|
Sign up to set email alerts
|

Profil penderita karsinoma sel ginjal (renal cell carcinoma) di RSUP Prof. Dr. R. D. Kandou Manado periode 2013-2015

Abstract: Renal cell carcinoma or Grawitz tumor is a tumor originating from the proximal tubular epithelial and 3% of malignant tumors in adults. The cause of this disease appeared was not accurately known but this disease can occur all over the world, depend on their ages, sex and race. Smoking and obesity are the most common cause of this tumor. This study was aimed to determine the profile of patients with renal cell carcinoma in the RSUP of Prof. Dr. R. D. Kandou Manado period 2013-2015 based on number of patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Melissa J, et al, In her research results stated that the most histopathological type in RCC is RCC clear cell. [11] Chandrasekaran et al, The results of his study also stated the same results, the results of his study that the clear cell RCC is the most histological type of RCC and the type of non-clear cell RCC histology each in 1 case. [14] In unclassified cases there is a component of squamous cell carcinoma (SCC).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Melissa J, et al, In her research results stated that the most histopathological type in RCC is RCC clear cell. [11] Chandrasekaran et al, The results of his study also stated the same results, the results of his study that the clear cell RCC is the most histological type of RCC and the type of non-clear cell RCC histology each in 1 case. [14] In unclassified cases there is a component of squamous cell carcinoma (SCC).…”
Section: Discussionsupporting
confidence: 53%
“…The strongest risk factors for RCC are smoking and smoking is more common in men than women and this might explain the higher proportion of men for RCC. [11,12] In this study grading assessment is done by using both grading because the assessment has different parameters. Gruh Fuhrman displays an assessment of mitosis while ISUP grading does not display an assessment of mitosis that only focuses on the core child.…”
Section: Discussionmentioning
confidence: 99%
“…Pasien yang terlalu lama berbaring akan berisiko mengalami kekakuan otot-otot tubuh, gangguan pada sirkulasi darah, pernafasan, peristaltik dan kandung kemih serta dekubitus (Kartawijaya, 2017). Penelitian yang dilakukan oleh Jenny Melisa (2016) menyimpulkan bahwa pada tahun 2013-2015 jumlah penderita karsinoma sel ginjal paling banyak terjadi tahun 2015 (62,5%), paling banyak terjadi direntang usia 51-65 tahun, terutama pada laki-laki dibandingkan perempuan dengan perbandingan (2 :1), tumor ginjal paling banyak adalah unilateral (100%) pada posisi dextra (56,25%). Para pasien paling sering mengalami nyeri pinggang yaitu 87,5%.…”
Section: Pendahuluanunclassified
“…The causes of RCC are currently still considered vague, complex, and multifactorial. However, several studies have found smoking and obesity to be common causes of RCC (Melisa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%